Avian Influenza (H7N9) Virus Infection in Chinese Tourist in Malaysia, 2014 - Timothy William; Bharathan Thevarajah; Shiu, Fee Lee; Maria Suleiman; Mohammad Saffree Jeffree; Jayaram Menon; Zainah Saat; Ravindran Thayan; Paul Anantharajah Tambyah; Tsin, Wen Yeo (2015)
Of the ≈400 cases of avian influenza (H7N9) diagnosed in China since 2003, the only travel-related cases have been in Hong Kong and Taiwan. Detection of a case in a Chinese tourist in Sabah, Malaysia, highlights the ease with which emerging viral respiratory infections can travel globally.